2020
DOI: 10.1111/bcp.14447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins and exercise on postprandial lipoproteins in metabolic syndrome vs metabolically healthy individuals

Abstract: Aims To determine if the combination of exercise and statin could normalize postprandial triglyceridaemia (PPTG) in hypercholesteraemic individuals. Methods Eight hypercholesteraemic (blood cholesterol 182 ± 38 mg dL−1; low‐density lipoprotein–cholesterol [LDL‐c] 102 ± 32 mg dL−1) overweight (body mass index 30 ± 4 kg m−2) individuals with metabolic syndrome (MetS) were compared to a group of 8 metabolically healthy (MetH) controls (blood cholesterol 149 ± 23 mg dL−1; LDL‐c 77 ± 23 mg dL−1, and body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
(36 reference statements)
0
18
0
1
Order By: Relevance
“… 11 Publications on the effects of statins on PPTG levels have been accumulating in the past 2 decades, and now there are enough studies to assess the strength of this secondary but clinically relevant effect of statins. 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Publications on the effects of statins on PPTG levels have been accumulating in the past 2 decades, and now there are enough studies to assess the strength of this secondary but clinically relevant effect of statins. 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…This blood sample was used as a baseline for the calculations of fasted metabolite levels. After 65 min of lying in a quiet room, (22 ± 1 °C and 25 ± 6% humidity) resting metabolic rate was assessed for 20 min, using indirect calorimetry (Quark b 2 , Cosmed, Italy). Fat oxidation was calculated according to Frayn's equations 20 with protein oxidation considered negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Statins are very effective in lowering cholesterol levels and are one of the safest drugs in clinical practice. Furthermore, statins can reduce postprandial hypertriglyceridemia 1–3 decreasing the risk of atherogenic plaque formation. Thus, in adults with a 10‐year atherosclerotic cardiovascular disease risk (Framingham Heart Study 4 ) of 20% or higher, statin therapy is indicated to reduce low‐density cholesterol levels (i.e., LDL‐c 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAG reduction of 22% (range 4 to 35%) [14,28,[37][38][39][40][41][42][43][44][45][46]29,[47][48][49][50][51][52][53][54][55][56]30,[57][58][59][60][61][62][63][64][65][66]31,67,68,[32][33][34][35][36]. iv.…”
Section: Accepted Manuscriptunclassified